(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Temperature, salinity and bottom sediment texture are important hydrographic parameters influencing the growth and survival of bivalves. Regular tidal flow, estuarine circulation and other allied hydrographic parameters in the Cochin Estuary has changed due to regular closure and opening of a salinity barrier at Thannemukkom. The environmental conditions on either side of the barrier (site A at south of bund and site B at north of bund) showed a clear and distinct variation in hydrographical parameters due to the existence of Thanneermukkom bund in between them. At site A the frequency of temperature fluctuation was high and the dominant environment was freshwater when compared with site B. Sediment texture at site A was sandy silt and at site B was silty sand. Even though a clear and perfect shift in modal values from month to month were not observed due to high rate of fishing mortality and regular breeding, monthly shift in modal value showed a slightly parabolic curve at both stations. The theoretical maximum length at Site A (54mm) closely agreed with the estimated maximum length from the population (52.6 mm), similarly at the Site B the theoretical maximum length was 52 mm and observed length was 50.8 mm. Growth rate of smaller clams were found to be higher than larger clams. All the growth models showed that organisms at Site B grow faster than station I, it is established by high “K” values at Site A ( 0.40) than Site B ( 0.32). It was observed that total mortality (fishing mortality) was higher at site B (7.2) than site A (3.16).